2017
DOI: 10.1002/mmce.21130
|View full text |Cite
|
Sign up to set email alerts
|

Tri-band composite cylindrical dielectric resonator antenna with hybrid mode excitation and cross-polarization suppression

Abstract: This communication investigates composite cylindrical dielectric resonator antenna (CDRA) for various wireless applications. Three important features of proposed antenna design are (i) realization of two different hybrid modes, that is, HEM11δ and HEM12δ mode in CDRA with the help of modified annular ring printed line (work as both magnetic dipole and electric dipole), both the hybrid modes support broadside radiation characteristics (ii) suppression of HEM21δ mode, in order to reduce the cross‐polarization le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…From Table 2, it can be observed that the proposed structure provides better impedance bandwidth than others. As we can see, the impedance bandwidth in [13] in lower frequency band is better than the proposed antenna structure. However, [13] is based on hybrid antenna technique, which does not provide complete advantages of DRA, i.e., gain fluctuations are very high.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…From Table 2, it can be observed that the proposed structure provides better impedance bandwidth than others. As we can see, the impedance bandwidth in [13] in lower frequency band is better than the proposed antenna structure. However, [13] is based on hybrid antenna technique, which does not provide complete advantages of DRA, i.e., gain fluctuations are very high.…”
Section: Resultsmentioning
confidence: 80%
“…As we can see, the impedance bandwidth in [13] in lower frequency band is better than the proposed antenna structure. However, [13] is based on hybrid antenna technique, which does not provide complete advantages of DRA, i.e., gain fluctuations are very high. The proposed radiator overcomes the drawback of hybrid radiators.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…If the length of the ground plane is changed, there occurs variation in return loss characteristics [6] . Better return loss is obtained when the length of the ground plane is changed from 50mm to 16mm.…”
Section: Fig 5: Return Loss ( ) Plotmentioning
confidence: 99%
“…The return loss plot of proposed design is shown in Fig7. Conformal strips are used for gain and bandwidth enhancement [6][7][8] .…”
Section: Fig 5: Return Loss ( ) Plotmentioning
confidence: 99%